PrODIMA: Programme outcomes data integration, management and analysis in OBE implementation / Asmidar Alias ...[et al.] - Alias, Asmidar; Mohamad Bhkari, Norshariza; Md Raus, Mohd Ikhsan; Abd Aziz, Muhd Eizan Syafiq; Ariffin, Kamisah (2010)
This innovation has been motivated by the complexities of the present practice in analysing the data of the Programme Outcomes in the Outcome-Based Education (OBE) implementation. The present practice requires manual data collection, management and analysis. The process, which involves more than one personnel, faces the risks of missing data and mismanagement of the data which could lead to misinterpretation of the data. In addition, not only the process is time consuming, it requires massive use of paper and support staff resources for data entry and analysis. Thus, this innovation proposes an electronic solution that helps to minimise the risks and the use of resources as well as providing sufficient, reliable and fast results which can be used as performance criteria at the continual quality improvement (CQI) level.